Protein kinase 2 of the giant sarcomeric protein UNC-89 regulates mitochondrial morphology and function - Yohei Matsunaga; Hiroshi Qadota; Nasab Ghazal; Leila Lesanpezeshki; Till Dorendorf; Jasmine C. Moody; Arnaud Ahier; Courtney J. Matheny; Siva A. Vanapalli; Steven Zuryn; Olga Mayans; Jennifer Q. Kwong; et al. (Communications Biology)
Abstract UNC-89 is a giant sarcomeric M-line protein required for sarcomere organization and optimal muscle function. UNC-89 contains two protein kinase domains, PK1 and PK2, separated by an elastic region. Here we show that PK2 is a canonical kinase expected to be catalytically active. C. elegans expressing UNC-89 with a lysine to alanine (KtoA) mutation to inactivate PK2 have normally organized sarcomeres and SR, and normal muscle function. PK2 KtoA mutants have fragmented mitochondria, correlated with more mitochondrially-associated DRP-1. PK2 KtoA mutants have increased ATP levels, increased glycolysis and altered levels of electron transport chain complexes. Muscle mitochondria show increased complex I and decreased complex II basal respiration, each of which cannot be uncoupled. This suggests that mutant mitochondria are already uncoupled, possibly resulting from an increased level of the uncoupling protein, UCP-4. Our results suggest signaling from sarcomeres to mitochondria, to help match energy requirements with energy production.